Pengukuran dan Evaluasi Produktivitas Pada Industri Kecil dan Menengah Menggunakan Pendekatan Green Productivity - Purba, Ari Pranata Primisa; Ahmad, Nofan Hadi; Lubis, Rizki Fadhillah (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2024)
This research was conducted in one of the Small and Medium Industries engaged in the agro-industry based on meat processing in Padang City by producing ready-to-eat packaged rendang, dry jerky and wet rendang. In the production process, the rendang SME produces waste in the form of solid waste and liquid waste. The purpose of this study was to determine the productivity of rendang SMEs both partially and totally using the green productivity approach so that it can be analyzed in the part that produces the potential for waste to be processed and increase the productivity of the SME. The results of this study are able to provide information on the description of the best productivity improvement strategy options, the level of productivity that has been achieved by the company, and the level of productivity resulting from the implementation of the selected strategy.